Pierre Bourdieu on the critical and humanistic-emancipatory role of sociology, intellectuals and the new european social movement - Mitrović, Ljubiša (Sociološki pregled, 2020)
The collage of Bourdieu’s debates and polemics (Signals of Lights Signals of Lights 2) most expressively illustrates how sociology of knowledge is organically connected with political sociology, or sociology of symbolic power his work;; the unity of theory and practice is achieved in an aspiration to reaffirm the engaged role of the sociologist’s profession, renew the role of intellectuals and form a new European social movement. Although he thought that today “it is not always easy to achieve the ideal of the collective intellectual”, which he aspired to identify with, Bourdieu hoped that his critical reflections and polemical interventions, as the “lit signals of lights”, may “serve as a useful weapon to all those who are trying to resist the neoliberal scourge… if not hoping to move a mobilization… at least to destroy the impression of unanimity that constitutes the essence of the symbolic picture of the dominant discourse” (Bourdieu, 2019, pp. 41-42).